2011
DOI: 10.1128/jb.01193-10
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Binding Properties of the Bacillus subtilis and Aeribacillus pallidus AC6 σ D Proteins

Abstract: D proteins from Aeribacillus pallidus AC6 and Bacillus subtilis bound specifically, albeit weakly, to promoter DNA even in the absence of core RNA polymerase. Binding required a conserved CG motif within the ؊10 element, and this motif is known to be recognized by region 2.4 and critical for promoter activity.In the course of efforts to define gene expression determinants from the thermophilic bacterium Aeribacillus pallidus AC6 (2, 18), we identified flagellin (Hag) as being among the most highly expressed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…The results from an EMSA‐based competition assay and a DNase I footprinting assay showed that B. subtilis σ B possesses core‐independent promoter −35 element binding specificity. The results are different to those reported for B. subtilis σ D . Possible reasons for the discrepancy are discussed.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results from an EMSA‐based competition assay and a DNase I footprinting assay showed that B. subtilis σ B possesses core‐independent promoter −35 element binding specificity. The results are different to those reported for B. subtilis σ D . Possible reasons for the discrepancy are discussed.…”
Section: Introductioncontrasting
confidence: 99%
“…We determined the existence of a core‐independent promoter‐specific binding activity of B. subtilis σ B in vitro by using an EMSA‐based competition assay and a footprinting assay. In contrast to the promoter −10 element binding specificity of the B. subtilis alternative σ factor, σ D , and the primary σ factor, σ A , the B. subtilis σ B binds specifically and preferentially to the −35 region of its cognate promoter DNA.…”
Section: Discussionmentioning
confidence: 94%
“…Hypersensitivity often invokes cooperative protein–protein interactions that are difficult to explain in the context of a sigma factor. σ D is unusual among the sigma factors, however, in that it binds to DNA in the absence of core RNA polymerase, and generates supershifted complexes that may indicate more than one protein bound at the promoter (Chen and Helmann, 1995; Bertero et al ., 1999; Sevim et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…103 This interaction may lead to the observed autoinhibition of promoter DNA binding by free primary sigma factors. 104 Autoinhibition has not been observed for interaction with the double-stranded promoter DNA of free sigma factors lacking region 1.1 by deletion 105 or naturally, 106,107 or for free σ 70 interacting with the NT strand of promoter DNA. 108 …”
Section: The Role Of σ70 In Promoter Interactions Open Complex Formamentioning
confidence: 97%